Pengaruh Variabel Makro terhadap Penerimaan Pendapatan Asli Daerah Kabupaten Karanganyar - Triani Triani; Yeni Kuntari (Jurnal Ilmiah Aset, 2010)
The research was quantitative research that used secondary data namely data of physical and documentary data. Later in this study, focusing only examined financial data Karanganyar District in the period 2003-2007. Method of analysis in this study used testing conducted by testing the effects of independent variables to the dependent variable. Analysis tools used in the study was quantitative analysis. Quantitative analysis was divided into two, namely the classical assumption test and multiple linear regression test.